Prevalence And Determinants Of Perinatal Depression Among Women In Lahore, Pakistan: A Cross-Sectional Study - Umar Aziz, Muhammad; Rafique, Kinza; Javed, Fizza; Qayyum, Abdul; Tahir , Wajiha; Javaid , Zuhaa; Sajjad, Areeba; Elsheikh, Aya Eltom Hajo; Ali , Syed Muhammad (Journal of Neonatal Surgery, 2025)
Background: Perinatal depression is a critical public health concern that can adversely affect both mother and child. However, little is known about its prevalence and determinants in urban Pakistani populations. Objective: To assess the prevalence and associated risk factors of perinatal depression among women attending maternity clinics in Lahore, Pakistan Methods: A cross-sectional study was conducted among 400 perinatal women using the Edinburgh Postnatal Depression Scale (EPDS). Logistic regression identified significant predictors. Results: The prevalence of perinatal depression was 38.5%. Significant associations were found with low income, unplanned pregnancies, poor spousal support, and prior mental health issues. Conclusion: High prevalence calls for routine screening and psychosocial support strategies in perinatal care programs.